The problems and prospects of Bumiputra travel agent in the era of globalization: With particular reference to Executive Travel & Tours (M) Sdn Bhd, Johor Bahru / Zawani Ismail - Ismail, Zawani (Faculty of Business and Management, 2005)
Tourism is one of the most important sectors in Malaysia. Increases in economic growth, disposable income and leisure time, political stability, and aggressive tourism campaigns, among other factors, have fueled the significant growth of tourism. This research reviews the problems and prospects of Bumiputra travel agent in the era of globalization. The future outlook is bright for Bumiputra travel agent and it is expected to maintain a high rate of growth well into the next century. Based on the researcher observation, Bumiputra travel agents have a big potential to improve their performance. Government played a big role in the development and growth of travel agent. They helped travel agent to experience continuous improvement by organizing international events and other important festivals. This is really significant with the growth of travel agent. This study will cover several aspects starting from the problems aroused from the travel agency itself, competitors, customers, airlines, prospects of Bumiputra travel agent, which subsequently, will conclude the performance level of Bumiputra travel agent among others. This research was conducted to scan the situation faced by Bumiputra travel agent. Hopefully, this research can provide some suggestions, actions or ides in identifying the ways that continuously improve the performance of Bumiputra travel agent. It also will assist Bumiputra travel agent to react towards the problem that was being traced while cooperating with customers, tour operators, and others.